Identification of heterophyllin B accumulation associated genes via WGCNA in Pseudostellaria heterophylla - Xu, Li-Yi; Wang, Shuai; Xu, Qing-Lin; Bu, Hong-Song; Wu, Ying-Ying; Su, Jing-Jing; Ye, Zu-Yun (Frontiers in Plant Science, 2025)
Pseudostellaria heterophylla (Miq.) Pax (P. heterophylla) is a perennial medicinal herb in which heterophyllin B (HB) serves as one of the primary bioactive compounds. Identifying genes associated with HB accumulation is crucial for breeding high-HB cultivars. In this study, we performed HPLC quantification and high-throughput RNA sequencing on three P. heterophylla accessions with differential HB content. Weighted gene co-expression network analysis (WGCNA) of the assembled transcriptome identified HB accumulation-associated modules, followed by qRT-PCR validation of candidate genes. HPLC quantification revealed significant variation in HB content among three samples (59.48 - 369.63 μg/g), with the sample ZS2 (a provincial-certified cultivars) identified as an HB-deficient genotype (t-test, p < 0.01 for all pairwise comparisons). De novo transcriptome assembly using Trinity generated a reference sequence comprising 114,625 transcripts, achieving 89.96 - 92.37% clean read mapping rates across samples. WGCNA clustered expressed genes into 55 modules, among which the yellow module (3,240 genes) showed the strongest positive correlation with HB accumulation. Gene Significance (GS) and Module Membership (MM) evaluation further identified 278 high-confidence candidate genes within this module. qRT-PCR validation using 180-day tissue-cultured samples confirmed one gene (g3166_i1) exhibiting perfect positive correlation with HB variation (kendall’s τ = 1). This study delineates transcriptomic signatures underlying HB divergence in P. heterophylla and provides actionable genetic targets for molecular breeding of high-HB cultivars.